A survey on genomic data by privacy-preserving techniques perspective. (August 2021) - B., Abinaya; S., Santhi
Graphical abstract: Highlights: Privacy concerns are needed regarding querying, accessing and, storage and computation of the genomic data. Privacy issues emerge by untrusted parties while outsourcing, as they reveal information/strategic plans of an individual. Many privacy-preserving techniques are used with cryptographic methods to strengthen security and privacy of genomic data. Abstract: Nowadays, the purpose of human genomics is widely emerging in health-related problems and also to achieve time and cost-efficient healthcare. Due to advancement in genomics and its research, development in privacy concerns is needed regarding querying, accessing and, storage and computation of the genomic data. While the genomic data is widely accessible, the privacy issues may emerge due to the untrusted third party (adversaries/researchers), they may reveal the information or strategy plans regarding the genome data of an individual when it is requested for research purposes. To mitigate this problem many privacy-preserving techniques are used along with cryptographic methods are briefly discussed. Furthermore, efficiency and accuracy in a secure and private genomic data computation are needed to be researched in future.